Hubungan Pola Asuh Pemberian Makan Terhadap Kejadian Stunting Pada Balita : The Relationship between Parenting and Feeding Patterns on the Incidence of Stunting in Toddlers - Sari, Agustina (Dohara POAJ, 2023)
Introduction: Stunting is a condition of the results of measuring the height of children <-2 based on a z-score or below the median standard of height growth against the age of WHO. The incidence of stunting is one of the nutritional problems that has an impact on inhibiting mental growth. One of the factors that causes stunting toddlers is the lack of nutritional intake in children who are very dependent on parents in feeding care. The purpose of this research is to see the relationship between feeding parenting and stunting in toddlers so that parents, especially mothers, can know the importance of maintaining feeding parenting so that children's nutritional intake is met and avoid stunting. Methods: Stunting is a condition of the results of measuring the height of children <-2 based on a z-score or below the median standard of height growth against the age of WHO. The incidence of stunting is one of the nutritional problems that has an impact on inhibiting mental growth. One of the factors that cause stunting toddlers is the lack of nutritional intake in children who are very dependent on parents in feeding care. Results: The data was obtained based on an analysis of 10 selected articles that showed that feeding parenting had a significant relationship with stunting in toddlers as evidenced by a p < 0,005 value. Discussion: Stunting is a condition of the results of measuring the height of children <-2 based on a z-score or below the median standard of height growth against the age of WHO. The incidence of stunting is one of the nutritional problems that has an impact on inhibiting mental growth. One of the factors that cause stunting toddlers is the lack of nutritional intake in children who are very dependent on parents in feeding care.